Musaddas Shaher Ashob of Dagh Delhvi: Analytical Study - Razia Majeed (بازیافت)
<span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Mirza Khan dagh Dehlvi is considered the last poet of Dehlvi school of classic Urdu poetry. He was a lover of beautiful faces. His entire life was spent composing poems of love and affection. In general perception, there is no despair in his poetry. But theTragedy of the war of Independence was very difficult time for Dagh Dehlvi, which he had expressed in his poem “Musaddas Shahr Aashob”. This poem is an elegy of destroyed and late Delhi of his times. Moreover, this poem is a unique piece of art that incorporates references to the contemporary history of that time. “Musaddas Shahr Aashob” is revealing significant information about the contemporary individual and collective attitudes of the people in Delhi during the War of Independence of 1857 and soon after that. In this poem Nawab Mirza Dagh Dehlvihimself is a representative of the mental state of the Delhi’s elite immediately after the war of Independence. Like many other people in Delhi, Dagh blamed the rebels for the destruction of Delhi. It was very difficult for the people of Delhi to admit their mistakes committed in the past. This poem is dominated by feelings of patriotism and love for Delhi. Dagh is a person associated with the culture and glorious past of Delhi. He said that those who attacked Delhi have done what is not permissible in any religion. Then he called those rebels “Mata Din” and “Ganga Din”.These words refer to Hinduism. Thus, this poem also strengthens the Two-Nations Theory in Indian Subcontinent. The theory that grew stronger and stronger in the coming times as the greatest truth in the history of Indo-Pak.